Study on Mechanical Properties of Organic and Non-Organic Fibre Panel Board - AZMI, ANIS SHAFIQAH; AHMAD NIZAL, NUR ATIQAH BASYIRAH; ISMAIL, PUTERI ME ALEEYANA; NGADIMAN, NORHAYATI (Multidisciplinary Applied Research and Innovation, 2022)
The panel board has been more in demand in construction industry contribute to increase the wood production to make the panel board for structural and decorative purposes. Panel board produced by wood and sawdust has weaknesses such as low tensile strength and flexural load. Currently, wood and sawdust in panelboard can be replaced by fibre materials. However, various type of fibre will indicate different mechanical properties of panelboard. Therefore, the objectives of this project are to compare the elasticity and strength of different type fibre in panel board using Modulus of Elasticity (MOE) and Modulus of Rupture (MOR) test and to identify the future potential uses in different type of fibre in construction industry. The main fibre materials used in this project are banana fibre, sugarcane bagasse fibre, coconut fibre as an organic fibre while for non-organic fibre is fibreglass. There are four phases in producing panel board which are material preparation, manufacturing the panel board, sample preparation for testing and data analysis by comparing each type of fibre panel board. Based on the results, fibreglass has the highest average MOE value of 8139.67 MPa and MOR average value of 187.370 MPa compared to other fibre panel board. This finding proved that fibreglass provide better strength property and able to increase durability of panel board. Finding from the survey interview, banana fibre, coconut fibre, sugarcane bagasse fibre and fiberglass had different potential uses that can be used in construction industry such as reinforced concrete, roof tiles and wall panelling while for inorganic fibre, it can be used in fiberglass-based composites and an admixture material in making the traffic light’s body. Hence, fiberglass is a better replacement material in producing panel board and all these fibres have various future potential as construction materials that can be applied in construction industry.